Pengembangan Media Video Pembelajaran Berbasis Canva Pada Mata Pelajaran IPA Kelas VI Sekolah Dasar - Atasya, Sindhu Marta; Priyanto, Wawan; Sundari, Riris Setyo (IAIN Kendari, 2024)
This research aims to develop interactive learning videos based on the Canva application for science education in sixth-grade elementary school classes. The study employs a Research and Development (R&D) methodology and was conducted at a public elementary school in Demak, with a total of 20 student subjects. Data were collected through expert validation questionnaires, teacher and student response questionnaires, interviews, documentation, and tests. The results of the media and content expert validations showed percentages of 96% and 98%, respectively, indicating very high feasibility. Both teachers and students assessed the developed media as very practical, with percentages of 96% and 98%, respectively. Analysis of the n-gain from student learning outcomes revealed a percentage of 92.5%, categorizing it as high. These findings indicate that the Canva-based Earth Rotation learning video for social studies in elementary schools is highly feasible and effective in improving students' cognitive learning outcomes. Keywords: Earth rotation, elementary school science, interactive learning videos